Investigation of the Drinking Water Quality of Some Residential Areas in Baghdad City - Karkh District - Abdalqader Mahdii , Beadaa; Jasim Mohammed, Ahmed; Abdalqader Mahdii, Sarah; Najeeb Ajaweed, Aseel (Iraqi Journal of Science, 2023)
The study aims to identify the acceptability of drinking water for human consumption depend on Iraqi specification and WHO standards. Samples collected monthly for each station from March to December2014. The samples collected from six stations distributed in Baghdad City, the first two stations located in al-Kadmyai area , the 3rd and 4th located in AL- Doora while the last two stations located in Al-Amryai area. The study measured physical, chemical and bacteriological factors. The measured parameters were ranged each for pH 6.63-7, turbidity 0.4-1.3NTU,TDS394.2-960mg/l,total hardness 259.1-578while Ca and Mg were 43-134,20.1-72 mg /l respectively. Other chemical parameters like chloride ranged from 56.8-184 mg/l and heavy metals ranged from 0-0.01,0-0.053,0.038mg/l for Pb+2,Cu+ and Fe+ respectively. The bacteriological examination included a total count for aerobic bacteria which is ranging from 0-10000 cell/ml, Coliform, and fecal coliform were ranged 0-3000, 0-300 cell/ml respectively. The results compared with standard limits and found some parameters exceeded the acceptable limits.